Pengembangan E-LKPD Berbantuan Website TopWorksheets untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Desi Nur Apriani; Resyi A. Gani; Nur Hikmah (Mataram University, 2026)
This study aimed to develop a TopWorksheets-assisted Electronic Student Worksheet (E-LKPD) on the topic Traditions and Culture of the Community Around Me, examine its feasibility, and determine its effectiveness in improving the critical thinking skills of fourth-grade elementary school students. This study employed the Research and Development (R&D) method using the ADDIE development model, consisting of the Analyze, Design, Develop, Implement, and Evaluate stages. The research subjects were 26 fourth-grade students at SDN Bantarkemang 6, Bogor City. The validation process involved a media expert, a language expert, a university subject-matter expert, and an elementary school teacher as the subject-matter expert. The validation results showed scores of 92% from the media expert, 100% from the language expert, 92% from the university subject-matter expert, and 96% from the teacher subject-matter expert, all categorized as highly feasible. The teacher response questionnaire obtained a score of 86%, categorized as very good, while the students' responses reached 95.77%, also categorized as very good. The effectiveness test yielded an N-Gain score of 0.78, which falls into the high category. Furthermore, the implementation results indicated that the TopWorksheets-assisted E-LKPD facilitated students in analyzing information, providing reasons, evaluating information, and drawing conclusions, thereby supporting the improvement of their critical thinking skills. The interactive features provided by TopWorksheets enabled students to engage actively in learning activities and complete structured tasks that encouraged higher-order thinking during the learning process. Based on these findings, the TopWorksheets-assisted E-LKPD is considered feasible, practical, and effective as an IPAS learning medium for improving the critical thinking skills of fourth-grade elementary school students.